Increasing students' enthusiasm and learning outcomes in the application of warm-up variations in physical education - Hidayat, Widhi (Universitas Suryakancana, 2024)
This study aims to increase students' enthusiasm and learning outcomes in learning Physical Education (PE), especially on physical fitness material, at SDN Pakis 1/368 Surabaya through the application of warm-up variations. The method used is Classroom Action Research (CAR) with a qualitative approach, with the research subjects being class 4A students. Data were collected through observation and learning outcome tests, and analyzed through the stages of planning, implementation, observation, reflection, and subsequent action. The results showed an increase in the average score of students' learning outcomes in the skill aspect from 81 in the initial stage to 89 in the second cycle, while in the attitude aspect from 80 to 90. The variety of warm-ups in PE learning has significantly improved students' enthusiasm and their learning outcomes. It is recommended that PE educators pay more attention to the integration of warm-up variations in learning to improve students' enthusiasm and overall learning outcomes.